Letter (copy) : Largo Caballero and others - Tewson, Vincent
013-0065-001 International. HVT/WJB/DT/109. 15th November, 1940. Mr. W. Carrillo, 7, Orme Court, LONDON, W.2. Dear Mr. Carrillo, LARGO CABALLERO AND OTHERS. We have duly received your letter of the 14th instant with regard to our old Comrade Largo Caballero and other leaders of the Spanish Trade Union Movement. We are very sorry indeed to learn of their grave position, and although our means for helping them are obviously limited to-day, we have taken measures with a view to inducing General Franco to exercise mercy in dealing with the former representatives of the Spanish people. We are also trying to have influence brought to bear upon the Vichy Government so that they will desist from handing over Spanish refugees to the Spanish Authorities. Yours sincerely, Assistant Secretary. 292/946/13/65